Pengembangan Modul Realistic Mathematics Education Bernilai Budaya Banten untuk Mengembangkan Kemampuan Literasi Matematis Siswa - Nurul Hilaliyah; Ria Sudiana; Aan Subhan Pamungkas (Universitas Syiah Kuala, 2019)
This research aimed to develop a textbook and an e-book of teaching materials based on Realistic Mathematics Education (RME) incorporating the value of Bantenese culture to develop mathematical literacy in social arithmetic; to examine the user's response to the textbook and e-book of teaching materials; and to identify students' mathematical literacy after using the textbook and e-book of teaching materials. The development research method used in this study refers to the research development model, which was initiated by Borg and Gall and adapted by Sugiyono into seven steps. Six expert tests from the material expert test and media expert test have carried out testing of the textbook and e-book teaching materials developed. The results of the study showed that the average quality of the teaching materials reached 85%, included in the 'good' category and the average of the evaluation aspect was 82%, included in the category of